Correction: The effects of one-night sleep deprivation and one-night recovery sleep on endurance cycling performance - Chiara Gattoni; Michele Girardi; Amir-Homayoun Javadi; Barry Vincent O’Neill; Samuele Maria Marcora (European Journal of Applied Physiology, 2026)

The effects of one-night sleep deprivation and one-night recovery sleep on endurance cycling performance - Chiara Gattoni; Michele Girardi; Amir-Homayoun Javadi; Barry Vincent O’Neill; Samuele Maria Marcora (European Journal of Applied Physiology, 2026)
Purpose Sleep deprivation (SD) seems to impair endurance performance. However, little research is available on the effects of SD in the context of repeated bouts of endurance exercise. The effect of recovery sleep on endurance performance is also poorly understood. Methods Twenty-six male amateur cyclists/triathletes (mean ± SD: age 30.5 ± 8.8 yr, $$\dot{\text{V}}{O}$$ V ˙ O 2peak 55.3 ± 4.9 mL/kg/min) were randomly allocated to SD and CONTROL groups and tested over 3 consecutive days. After baseline testing (day 1), the SD group did not sleep for 25 h (day 2) and slept normally the following night (day 3). The CONTROL group slept normally throughout the experiment. Endurance performance was assessed during 40-min moderate-intensity constant-workload cycling and 20-min time trial. Electroencephalography, questionnaires, and psychomotor vigilance task were used to assess sleepiness and vigilance before cycling. Ratings of perceived exertion (RPE), Feeling scale (FS), heart rate (HR), and blood lactate were assessed during cycling. Results Sleepiness and vigilance were impaired after SD ( p < 0.05), but returned to baseline after recovery sleep. RPE ( p = 0.023) and FS ( p = 0.013) assessed during the 40-min cycling were negatively affected by SD, but returned to baseline after recovery sleep. HR and blood lactate were not affected by SD. No significant interaction effect was observed on time-trial work. Conclusion In the context of 3 consecutive days of endurance cycling, 25-h SD negatively affected moderate-intensity performance through higher RPE, but did not affect the 20-min time trial. One-night recovery sleep was sufficient to restore moderate-intensity endurance cycling performance.

Ischemic preconditioning of the muscle reduces the metaboreflex response of the knee extensors - Luca Angius; Benjamin Pageaux; Antonio Crisafulli; James Hopker; Samuele Maria Marcora (European Journal of Applied Physiology, 2022)
Purpose This study investigated the effect of ischemic preconditioning (IP) on metaboreflex activation following dynamic leg extension exercise in a group of healthy participants. Method Seventeen healthy participants were recruited. IP and SHAM treatments (3 × 5 min cuff occlusion at 220 mmHg or 20 mmHg, respectively) were administered in a randomized order to the upper part of exercising leg’s thigh only. Muscle pain intensity (MP) and pain pressure threshold (PPT) were monitored while administrating IP and SHAM treatments. After 3 min of leg extension exercise at 70% of the maximal workload, a post-exercise muscle ischemia (PEMI) was performed to monitor the discharge group III/IV muscle afferents via metaboreflex activation. Hemodynamics were continuously recorded. MP was monitored during exercise and PEMI. Results IP significantly reduced mean arterial pressure compared to SHAM during metaboreflex activation (mean ± SD, 109.52 ± 7.25 vs. 102.36 ± 7.89 mmHg) which was probably the consequence of a reduced end diastolic volume (mean ± SD, 113.09 ± 14.25 vs. 102.42 ± 9.38 ml). MP was significantly higher during the IP compared to SHAM treatment, while no significant differences in PPT were found. MP did not change during exercise, but it was significantly lower during the PEMI following IP (5.10 ± 1.29 vs. 4.00 ± 1.54). Conclusion Our study demonstrated that IP reduces hemodynamic response during metaboreflex activation, while no effect on MP and PPT were found. The reduction in hemodynamic response was likely the consequence of a blunted venous return.

Reply to: The parabolic power–velocity relationship does apply to fatigued states - Samuele Maria Marcora; Walter Staiano (European Journal of Applied Physiology, 2011)

Erratum to: The limit to exercise tolerance in humans: mind over muscle? - Samuele Maria Marcora; Walter Staiano (European Journal of Applied Physiology, 2010)

Reply to: What limits exercise during high-intensity aerobic exercise? - Samuele Maria Marcora; Walter Staiano (European Journal of Applied Physiology, 2010)

The parabolic power–velocity relationship does not apply to fatigued states - Samuele Maria Marcora; Walter Staiano (European Journal of Applied Physiology, 2010)

The limit to exercise tolerance in humans: mind over muscle? - Samuele Maria Marcora; Walter Staiano (European Journal of Applied Physiology, 2010)